Histone H3 Cleavage in Severe COVID-19 ICU Patients - Huckriede, Joram; de Vries, Femke; Hultström, Michael; Wichapong, Kanin; Reutelingsperger, Chris; Lipcsey, Miklos; Garcia de Frutos, Pablo; Frithiof, Robert; Nicolaes, Gerry A. F. (Frontiers in Cellular and Infection Microbiology, 2021)
The severity of coronavirus disease 19 (COVID-19) is associated with neutrophil extracellular trap (NET) formation. During NET formation, cytotoxic extracellular histones are released, the presence of which is linked to the initiation and progression of several acute inflammatory diseases. Here we study the presence and evolution of extracellular histone H3 and several other neutrophil-related molecules and damage-associated molecular patterns (DAMPs) in the plasma of 117 COVID-19-positive ICU patients. We demonstrate that at ICU admission the levels of histone H3, MPO, and DNA-MPO complex were all significantly increased in COVID-19-positive patients compared to control samples. Furthermore, in a subset of 54 patients, the levels of each marker remained increased after 4+ days compared to admission. Histone H3 was found in 28% of the patients on admission to the ICU and in 50% of the patients during their stay at the ICU. Notably, in 47% of histone-positive patients, we observed proteolysis of histone in their plasma. The overall presence of histone H3 during ICU stay was associated with thromboembolic events and secondary infection, and non-cleaved histone H3 was associated with the need for vasoactive treatment, invasive ventilation, and the development of acute kidney injury. Our data support the validity of treatments that aim to reduce NET formation and additionally underscore that more targeted therapies focused on the neutralization of histones should be considered as treatment options for severe COVID-19 patients.